Effect of Principal Leadership Style Women's and Cultural Organization of Work Ethos Teachers - Bintara Bintara; Widyamike Gede Mulawarman; Azainil Azainil (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
This study aims to determine the effect of the leadership style of female principals and organizational culture on the work ethic of junior high school teachers in Samarinda. This research is a quantitative study using a correlational method. The total population was 126 teachers and the research sample was 96 teachers consisting of three different schools, namely SMPN 5, 10 and 38 Samarinda. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used descriptive and inferential statistics, with simple linear regression, multiple regression, and correlation analysis. The results showed that the leadership style of femaleschool principals (X1) had a significant effect on 79.4%. This shows that the better the leadership style of the female school principal, the better the work ethic of the teacher will be. It is also known that organizational learning (X2) has a significant effect of 39.4%. This shows that the better the school organizational culture, the better the work ethic of the teacher will be. Simultaneously the competence of school principals (X1) and organizational culture (X2) has a significant effect on teacher work ethics (Y) by 81.8%. This indicates that the better the leadership style of female principals and organizational learning, the more teachers work ethic will be good.